An Empirical Study on Korean Packaged Halal Food Manufactures: Muslim Millennial Consumers' Purchase Intention - Zahra, Inas Afifah; Said, Muhammad; Muhammad, Firman (CV ODIS, 2023)
This study aims to identify millennial Muslim consumers' perceptions of South Korean halal packaged food products and examine the relationship of each determinant to these food products. The research method used is a quantitative survey with a multiple linear regression data analysis method. The results showed that the primary perception of millennial Muslim consumers' intention to buy South Korean halal packaged food is the halal logo or certification. The factors determining this purchase intention do not fully have a positive and significant effect. Factors that have a positive and significant influence include; halal awareness, halal logo/certification, and product ingredients. While the factors of religious belief and exposure do not positively and significantly influence purchasing intentions. This study recommends that businesses engaged in the South Korean food sector with Muslims as their target customers follow halal principles, such as managing halal certification and including halal labels, raw material information, and processing methods of product/food packaging.